2019
DOI: 10.1093/nar/gkz1112
|View full text |Cite
|
Sign up to set email alerts
|

Specific enhancer selection by IRF3, IRF5 and IRF9 is determined by ISRE half-sites, 5′ and 3′ flanking bases, collaborating transcription factors and the chromatin environment in a combinatorial fashion

Abstract: IRF3, IRF5 and IRF9 are transcription factors, which play distinct roles in the regulation of antiviral and inflammatory responses. The determinants that mediate IRF-specific enhancer selection are not fully understood. To uncover regions occupied predominantly by IRF3, IRF5 or IRF9, we performed ChIP-seq experiments in activated murine dendritic cells. The identified regions were analysed with respect to the enrichment of DNA motifs, the interferon-stimulated response element (ISRE) and ISRE half-site variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…This region was also termed P31 because these two PRDs act as a functional unit, an enhanson [ 38 ]. Recent in-depth analysis of the binding requirements of different IRF members suggests that, in addition to a slight variation of the core GAAA recognition motif, the flanking regions along with the spacing in between the IRF-Es contribute to specific binding of distinct IRF family members, here favouring recruitment of IRF3 and IRF7 [ 81 , 82 ]. The nucleotide sequence of the IFNβ enhancer causes a bent conformation of the DNA helix in inactive conditions and in this way drives cooperative binding of the transcription factor heterodimers upon stimulation [ 68 ].…”
Section: A Complex Performance—stimulus-induced Assembly Of the Ifmentioning
confidence: 99%
See 1 more Smart Citation
“…This region was also termed P31 because these two PRDs act as a functional unit, an enhanson [ 38 ]. Recent in-depth analysis of the binding requirements of different IRF members suggests that, in addition to a slight variation of the core GAAA recognition motif, the flanking regions along with the spacing in between the IRF-Es contribute to specific binding of distinct IRF family members, here favouring recruitment of IRF3 and IRF7 [ 81 , 82 ]. The nucleotide sequence of the IFNβ enhancer causes a bent conformation of the DNA helix in inactive conditions and in this way drives cooperative binding of the transcription factor heterodimers upon stimulation [ 68 ].…”
Section: A Complex Performance—stimulus-induced Assembly Of the Ifmentioning
confidence: 99%
“…Further cooperativity is mediated by the P31 sequence that ensures concerted binding of ATF2-c-Jun and IRF3 [ 97 , 98 ] and by CBP/p300-mediated interactions within the enhanceosome complex [ 38 , 90 ]. Clustering of IRF3 target regions with binding motifs for NF-κB or other transcription factors along with low chromatin accessibility in steady-state conditions was recently described as a common feature of IRF3-DNA interactions, implying an obligatory collaborative binding mode of IRF3 that promotes access to chromatin [ 82 ]. At the IFNβ enhancer, a total of four IRF3/7 molecules bound to four IRF-Es in tandem are required to induce gene expression of a luciferase-based IFNβ-reporter plasmid in the commonly used human embryonic kidney cell line HEK293T [ 99 ].…”
Section: A Complex Performance—stimulus-induced Assembly Of the Ifmentioning
confidence: 99%
“…One of the explanations of this result is that the specific binding reactions between TFs and enhancers are not strong enough to be detected. Moreover, given that the gene regulatory network is complex and that TFs could collaborate with each other ( Csumita et al, 2020 ; Theeuwes et al, 2020 ), indirect interactions might exist between the above TFs and enhancers in our study.…”
Section: Discussionmentioning
confidence: 88%
“…However, the luciferase assay did not identify obvious enhancer activity of tnni1b-ECR183-h179. Considering the complex gene regulatory network and the collaboration between TFs ( Csumita et al, 2020 ), tnni1b-ECR183-h179 might bind to repressive TFs to decrease the expression of luciferase in this study. The truncated fragment tnni1b-ECR183-h84 showed skeletal muscle-specific enhancer activity.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have shown that IRF9 is associated with unphosphorylated STATs (U-ISGF3) or is expressed independently of STAT1, which leads to altered gene expression profiles [ 17 , 18 , 19 , 20 ]. Studies on IRF binding regions have detected dominant clusters for IRF3, IRF5, or IRF9 based on occupancies and revealed that the affinity of IRF9 to ISRE variants is more specific to the sequence 5′-GAAANNGAAACT-3′ [ 21 ].…”
Section: Introductionmentioning
confidence: 99%